CSR Moderation in the Influence of Intellectual Capital and Transformational Leadership on Organizational Performance - I Gusti Ayu Asri Pramesti; Nicholas Renaldo; Ni Putu Yuria Mendra; Ida Ayu Budhananda Munidewi (www.amertainstitute.com, 2025)
The Village Credit Institution (LPD) is an institution managed by the laws and regulations of Bali. The LPD promotes the traditional village economy in economic, social, and cultural aspects. This study aims to analyze the role of CSR in strengthening intellectual capital and transformational leadership on organizational performance. This study used 246 LPD heads as respondents from 246 LPD in Bali Province. Data was collected by distributing questionnaires and interviews with some LPD heads. Data were analyzed using a structural equation model with the Partial Least Squares application. The results indicate that intellectual capital has a positive influence on LPD performance. Transformational leadership has a positive influence on LPD performance. CSR does not strengthen intellectual capital and transformational leadership in organizational performance. The findings suggest that LPD with transformational leaders and intellectual capital are crucial for maintaining the sustainability of LPD. This study has limitations in the direct distribution of questionnaires because respondents were reluctant to fill them out via Google Forms. This study has implications that can expand knowledge and provide information for LPD by considering intellectual capital and transformational leadership in improving organizational performance and sustainability.